Synthesis of Substituted Phenyl N-(2-hydroxybenzyl)-N-Methylcarbamates - JaromÃƒÂr KavÃƒÂ¡lek; JaromÃƒÂr Mindl; Petr Ã…Â imÃ…Â¯nek; OldÃ…Â™ich HrabÃƒÂk (Molecules, 2002)
Thirteen previously unreported substituted phenyl N-(2-hydroxybenzyl)-Nmethylcarbamates were prepared by the reaction of substituted 2-hydroxybenzyl-Nmethylamines with phenyl chlorocarbonates. They were identified by their 1H- and 13C-NMR spectra.